A Review on the Herbs Combination for Phlegm Disease Treatment According to Dan Xi Xin Fa - Leong, Wen Jun; Leong, May Ho; Heng, Aik Teng; Wong, Ling Shing (INTI International University, 2019)
Zhu Dan Xi 朱丹溪 was considered one of the greatest scholar in Jin-Yuan dynasty. One of his outstanding therapeutic principle is in the treatment of phlegm diseases. Zhu Dan Xi’s therapeutic principle in treating phlegm disease can be learned by analyzing the statistical data of the herbs’ medicinal characteristic and herbs’ combination, as stated in Dan Xi Xin Fa [丹溪心法]. Results regarding the usage of herbs and their medicinal characteristics were systematically recorded in Shen Nong Ben Cao Jing as well [神农本草经]. In this paper, the principle of treating phlegmatic syndrome according to the experience of Zhu Dan Xi is discussed. The principle of treating qi in order to cure phlegmatic syndrome is focused. The herbs with acrid and bitter tastes were used by him to cure the disease. By combination of these two types of herbs, qi can be regulated thorough the body. The movement of qi will help in curing the diseases.